Development and evaluation of paclitaxel nanoemulsion for cancer therapy. (20th April 2020) - Shakhwar, Sara; Darwish, Rana; Kamal, Mohammad M.; Nazzal, Sami; Pallerla, Sandeep; Abu Fayyad, Ahmed
Abstract: Tocosol™ is a tocopherol-based paclitaxel (PTX) nanoemulsion consisting of α-tocopherol (α-T) isomer of vitamin E as a solubilizer and vitamin E TPGS as the primary emulsifier. Despite its positive attributes in early clinical studies, it failed the pivotal phase III clinical trials. The long-term goal of this work was to reformulate Tocosol™. In this study, Tocosol™ formulation was optimized by replacing the α-T isomer with the more pharmacological active isomer γ-tocotrienol (γ-T3 ), and the surfactant vitamin E TPGS was replaced with in-house designed PEGylated γ-T3 surfactant. The reformulated paclitaxel γ-T3 /PEGylated γ-T3 -based nanoemulsion was significantly more active against pancreatic tumor cell lines than α-T/Vitamin E TPGS based formulation (IC50 = 0.5 μM and 1.1 μM, respectively). Furthermore, the reformulated product showed an average size of 220 ± 6 nm with surface charge equal to −42 ± 2 mV. The optimized product was physically and chemically stable over 6 months per ICH storage condition guidelines.